2021
DOI: 10.21203/rs.3.rs-654294/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DRP1-Mediated Mitochondrial Fission Regulates the Lung Epithelial Response to Allergen

Abstract: Background: Mitochondria regulate a myriad of cellular needs and functions. Dysregulation of mitochondrial control within airway epithelial cells has been implicated in the pro-inflammatory response to allergens in asthmatics. Because of their multifaceted nature, mitochondrial structure needs to be tightly regulated through fission and fusion. Dynamin Related Protein 1 (DRP1), a cytosolic GTPase, is a key driver of mitochondrial fission. During allergic asthma, airway epithelial mitochondria appear smaller an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…A similar phenomenon was observed in the airway epithelium stimulated by PM2.5, accompanied by a decrease in mitochondrial oxidative phosphorylation (OXPHOS) and glycolysis 55 . In house dust mite‐induced asthma, downregulation of mitochondrial fission by knockdown of DRP1 increased the inflammatory response and cell death, and aggravated airway mucus hypersecretion and airway hyperresponsiveness 56 . These results indicated that DRP1 had different effects on inflammation due to different stimuli of pathological processes in the lung.…”
Section: Mitochondrial Dysfunction In Copd Is Related To Lipid Metabo...supporting
confidence: 58%
See 1 more Smart Citation
“…A similar phenomenon was observed in the airway epithelium stimulated by PM2.5, accompanied by a decrease in mitochondrial oxidative phosphorylation (OXPHOS) and glycolysis 55 . In house dust mite‐induced asthma, downregulation of mitochondrial fission by knockdown of DRP1 increased the inflammatory response and cell death, and aggravated airway mucus hypersecretion and airway hyperresponsiveness 56 . These results indicated that DRP1 had different effects on inflammation due to different stimuli of pathological processes in the lung.…”
Section: Mitochondrial Dysfunction In Copd Is Related To Lipid Metabo...supporting
confidence: 58%
“…55 In house dust mite-induced asthma, downregulation of mitochondrial fission by knockdown of DRP1 increased the inflammatory response and cell death, and aggravated airway mucus hypersecretion and airway hyperresponsiveness. 56 These results indicated that DRP1 had different effects on inflammation due to different stimuli of pathological processes in the lung.…”
Section: Mitochondrial Dysfunction In Copd Is Related To Lipid Metabo...mentioning
confidence: 90%